(untitled) (UUM Journal of Legal Studies, 2013)
South Africa was under the apartheid rule for around fifty years. Apartheid was formally established by the National Party when it came to power in 1948. In terms of the apartheid policy, the government belonged to the White people who enjoyed all human rights and were entitled to rule the country to the detriment of the Black people despite the latter constituting the overwhelming majority of the population. The apartheid regime eventually came to an end in the early 1990s. Following the ending of the dictatorial regime, a new Constitution was adopted and the first democratic elections were held in South Africa. [T]his paper reflects on the road that South Africans have gone from Apartheid to democracy and good political governance, on what they have achieved as well as the challenges and prospects for democratic governance in the country. Keywords: South Africa; apartheid; Constitution; governance; democracy and human rights.